Enhanced and Optically Switchable Proton Conductivity in a Melting Coordination Polymer Crystal. (10th April 2017) - Nagarkar, Sanjog S.; Horike, Satoshi; Itakura, Tomoya; Le Ouay, Benjamin; Demessence, Aude; Tsujimoto, Masahiko; Kitagawa, Susumu
Abstract: The melting behavior of a coordination polymer (CP) crystal was utilized to achieve enhanced and optically switchable proton conductivity in the solid state. The strong acid molecules (triflic acid) were doped in one‐dimensional (1D) CP, [Zn(HPO4 )(H2 PO4 )2 ](ImH2 )2 (ImH2 =monoprotonated imidazole) in the melt state, and overall enhancement in the proton conductivity was obtained. The enhanced proton conductivity is assigned to increased number of mobile protons and defects created by acid doping. Optical control over proton conductivity in the CP is achieved by doping of the photo acid molecule pyranine into the melted CP. The pyranine reversibly generates the mobile acidic protons and local defects in the glassy state of CP resulting in the bulk switchable conductivity mediated by light irradiation. Utilization of CP crystal in liquid state enables to be a novel route to incorporate functional molecules and defects, and it provides a tool to control the bulk properties of the CP material.